Imagens das juventudes: uma mirada sobre o comportamento midiático-digital dos jovens de Bauru - Sousa, Juliano Ferreira de [UNESP] (2015)
Understanding the generational cycle is to think the very idea of youth!. Changes in cultural paradigms and behaviors of vanguard, have, generally, gained a boostoriginated among the youngsters. Concerning to this matter, much is said about the existence of a 'digital youth', which makes use of digital-media devices, and is especially inserted in connected contexts. This group, hardly binds to the media the same way their parents or their grandparents did, and keeps on reconfiguring the cultural and communicative practices. This research aims to propose a study of what these communication and digital practices of young connected people, which inhabit in the city of Bauru (SP). Likewise, we also inquire about the established relationships and what is the kind of media exchange with previous generations have been built. To answer these questions, we here propose a study on the evolution concerning the concepts of 'generation' and 'youth, giving particular attention to the reality in Latin America and its socio and cultural specifities. As a research subject in the matter of MastersDissertation, youngsters were selected among those withaccess tointernet and digital technology, residents in the city of Bauru (SP), between 15 and 29 years-old, a profile proposed by the 'Statute of Youth' (BRAZIL, 2013). A questionnaire for the chosen audience had been given to them, and applied online, mixing objective and subjective questions (with possible open and closed answers and control questions) to enable the quantitative and qualitative analyzes. Topics have been created for specific studies, in order to facilitates the separation of the data. Then we have checked if the communication-media profile found was the same as thatonespresented in the bibliography support. Therefore, we investigated the feasibility of the employment of terms such as 'Internet Generation and / or 'Digital Genration' for those youngsters. The concepts of Generation and...